Toruń z oddali (migawki wspomnień) - Kabzińska, Iwona (Auto/biograficzne aspekty praktyk poznawczych, 2016)
The Authoress uses snapshots of memories to create an emotional story about her meetings with Toruń; places, people and events important for her; and life going on between Toruń and Warsaw. She also shares her experiences related to working as a member of the academic staff at the Department of Ethnology and Cultural Anthropology at the University of Toruń (between 2000 and 2011). The text contains such thematic threads as: “familiarity” and “strangeness”, stability and variability (passing away), sense of community and solitude.